2021
DOI: 10.21203/rs.3.rs-755879/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covid-19 vaccine-induced antibodies are attenuated and decay rapidly in infliximab treated patients

Abstract: To inform healthcare policy for immunosuppressed patients there is a need to define SARS-CoV-2 vaccine responses. Here we report SARS-CoV-2 vaccine-induced antibody and T cell responses in patients treated with anti-tumour necrosis factor (anti-TNF), a commonly used biologic in inflammatory diseases, compared to patients treated with vedolizumab, a gut-specific antibody targeting integrin a4b7 that does not impair systemic immunity. In anti-TNF recipients, the magnitude of anti-SARS-CoV2 antibodies was reduced… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Other studies measuring humoral responses following two doses of COVID-19 vaccines have corroborated our findings in patients receiving anti-TNF therapy (eg, infliximab), although, in general, these studies have reported a more modest reduction in anti-SARS-CoV-2 spike protein antibody concentrations. 19,20,26 However, there are important differences between those studies and our study. Most previous studies have reported serological responses elicited exclusively by mRNA COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Other studies measuring humoral responses following two doses of COVID-19 vaccines have corroborated our findings in patients receiving anti-TNF therapy (eg, infliximab), although, in general, these studies have reported a more modest reduction in anti-SARS-CoV-2 spike protein antibody concentrations. 19,20,26 However, there are important differences between those studies and our study. Most previous studies have reported serological responses elicited exclusively by mRNA COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 55%
“…Finally, another potential limitation of this study is that we looked at humoral immunity, but not cell-mediated immunity. There has been some work on T-cell responses after SARS-CoV-2 vaccination in immunocompromised patients with IBD, 26,30 but the extent to which such responses correlate with humoral immunity across the spectrum of immunosuppressive therapies used in IBD is yet to be fully elucidated. A key priority of future work will be to probe the effect of COVID-19 vaccines on antigen-specific T-cell responses in the VIP cohort.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with a recent small study from Geissen et al 13 who showed decreased responses and waning immunity with anti-TNF agents in 23 IMID patients at 6 months post dose 2, and also confirmed with a larger cohort in a recent pre-print. 17 In our study, the vaccine dose interval was a median of 60.5 days rather than the standard 21 or 28 days used in the other studies, which could impact the results. Some limitations of our study are the small numbers of study subjects in some of the groups and grouping together of drugs by class.…”
Section: Discussionmentioning
confidence: 93%
“…7,11,13,14,16 A small study of 23 IMID patients showed that patients on anti-TNF therapy have greater waning of humoral immunity compared to healthy controls, 13 as confirmed in a larger study still in preprint. 17…”
Section: Introductionmentioning
confidence: 99%
“…4 The most recent data indicate that vaccinated IBD patients are well-protected against severe COVID-19 infection or death. 5,6 Thus, it is strongly recommended that unvaccinated IBD patients should be vaccinated as soon as possible.The evidence suggests that IBD patients receiving immunemodifying therapies may exhibit attenuated immune responses after vaccination, and protection against SARS-CoV-2 infection may wane over time. In a large-scale IBD cohort study performed in the UK (CLARITY-IBD), patients on infliximab evidenced 4-to 6-fold lower antibody levels than those of ve-…”
mentioning
confidence: 99%